Age and Sex Composition of Nepal Spotlighting by Provinces: A Trend Analysis (2001-2031) - Karki, Rita Devi (Tribhuvan University Journal, 2018)
Age and sex structure of population of particular region is key determinants for development. The population of Nepal is in transition phase due to the decreasing trend of the birth and death rates; as a result, the situation of demographic windows of opportunity is started in the country. However, the demographic window of opportunity as human resources of Nepal is being magnetized and used by different foreign countries in the world. So to take advantage of economic growth, it needs to invest in the youth of the country with consideration of gender equality. This paper explores the working age population, dependency ratio, index of ageing and sex ratio by provinces which has not been studied yet in the country. The data for this study were drawn from National Report 2001 and 2011 censuses and calculated by using Microsoft Excel. The population was projected by using exponential growth function for 2031. The working age population is growing in Nepal in all provinces except province six. It will arrive at in 63.0 percent at national level and the highest (77.3 %) in province three by 2031. The data seem to be interesting that the working age population of female is higher than male in all the years of the censuses. Although the ageing population is in the increasing trend, the overall dependency ratio is decreasing in almost all provinces. The problem of brain drain and issue of gender equality and equity in acceleration of nation’s development are considerable population management matters in Nepal.